2005
DOI: 10.1159/000085585
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Elevation of C-Reactive Protein May Predict Cardiac Hypertrophy and Dysfunction in Patients Maintained on Hemodialysis

Abstract: Background: C-reactive protein (CRP), which reflects chronic inflammation, is a strong predictor of cardiovascular mortality in hemodialysis patients. We investigated whether persistent elevation of CRP is associatedwith cardiac function and morphology in patients maintained on hemodialysis. Methods: Predialysis high-sensitivity CRP (hs-CRP) was measured twice at an interval of 3 weeks in 52 stable hemodialysis patients, and echocardiographic studies were performed. Results: 25 patients showed persistent eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 30 publications
4
26
1
2
Order By: Relevance
“…The present observation of an independent association between categories of CRP level and LVMI is consistent with previous findings (15,19), and the present study extended these observations for CRP to essential hypertension. A raised baseline CRP value has been associated with inflammation, endothelial dysfunction (14), obesity (14), the metabolic syndrome (30,31), diabetes mellitus (32), insulin resistance (13), and severity of hypertension (33), and thus, various metabolic disorders may occur with increasing CRP level, and simultaneously promote an increase in LV mass.…”
Section: Discussionsupporting
confidence: 93%
“…The present observation of an independent association between categories of CRP level and LVMI is consistent with previous findings (15,19), and the present study extended these observations for CRP to essential hypertension. A raised baseline CRP value has been associated with inflammation, endothelial dysfunction (14), obesity (14), the metabolic syndrome (30,31), diabetes mellitus (32), insulin resistance (13), and severity of hypertension (33), and thus, various metabolic disorders may occur with increasing CRP level, and simultaneously promote an increase in LV mass.…”
Section: Discussionsupporting
confidence: 93%
“…In ESRD patients, chronic inflammation, as expressed by increased CRP levels, has been identified as accelerating atherosclerosis (39). Data from several studies have demonstrated that elevated levels of the acute-phase reactant CRP were associated with increased cardiovascular events and atherosclerosis (decreased ABI) (40,41). In the present study, there was no correlation between high-sensitivity CRP and ABI Ͻ0.9 or vascular access failure.…”
Section: Discussioncontrasting
confidence: 50%
“…Elevated hs-CRP levels have been reported as being a strong predictor of cardiovascular mortality and atherosclerosis in ESRD patients [5, 6]. Also, hs-CRP levels correlate with the length of dialysis in ESRD patients alluding to a strong involvement of the protein in the inflammatory process [7].…”
Section: Introductionmentioning
confidence: 99%
“…Also, hs-CRP levels correlate with the length of dialysis in ESRD patients alluding to a strong involvement of the protein in the inflammatory process [7]. This is important given recent reports linking altered hs-CRP levels with cardiac hypertrophy and increased arterial stiffness [5, 6, 8]. Ample evidence also exists to support a direct role of hs-CRP in inflammatory cell recruitment and endothelial dysfunction by upregulating endothelial cell adhesion molecules [9].…”
Section: Introductionmentioning
confidence: 99%